A Reference Model for Smart Tailor Applications Development - Mohd, Haslina; Dahari, Rohaya; Mat Aji, Zahurin; Yusop, Nor Iadah; Marzuki, Zaharin (International Journal of Supply Chain Management, 2018)
Practitioners in the Malaysian fashion and garment industry, particularly, tailors and fashion designers are facing various challenges in satisfying the supply and demands of their garment products because of them are still providing their products and services through traditional ways. In order to sustain their businesses and remain competitive, they need to transform their current practice in fulfilling customers’ demands. In tackling this issue, this paper presents a reference model of Smart Tailor application for the garment industry practitioners. This is proposed to help reduce the time and increase the efficiency in the fulfilment of the clothing supply and demand. The study adopted the Inception and Elaboration phases of the Rational Unified Process (RUP) in developing the reference model. Starting with the Inception phase, the goal and business requirements were identified using the business model canvas approach, whilst the list of requirements was verified. In the Elaboration phase, the list of requirements was transformed into Smart Tailor design components using the Unified Modelling Language approach. Finally, the verified requirements and design components become a Reference Model of Smart Tailor for garment industry practitioners. The reference model may contribute to garment industry practitioners such as software developers, tailors, and fashion designers as well as to researchers and decision makers in the garment industry domain.